Enhancing Long‐Term Device Stability Using Thin Film Blends of Small Molecule Semiconductors and Insulating Polymers to Trap Surface‐Induced Polymorphs - Salzillo, Tommaso; Campos, Antonio; Babuji, Adara; Santiago, Raul; Bromley, Stefan T.; Ocal, Carmen; Barrena, Esther; Jouclas, Rémy; Ruzie, Christian; Schweicher, Guillaume; Geerts, Yves H.; Mas‐Torrent, Marta (Advanced functional materials, 2020)
The lack of long‐term stability in thin films of organic semiconductors can often be caused by the low structural stability of metastable phases that are frequently formed upon deposition on a substrate surface. Here, thin films of 2,7‐dioctyloxy[1]benzothieno[3,2‐b]benzothiophene (C8O‐BTBT‐OC8) and blends of this material with polystyrene by solution shearing are fabricated. Both types of films exhibit the metastable surface‐induced herringbone phase (SIP) in all the tested coating conditions. The blended films reveal a higher device performance with a field‐effect mobility close to 1 cm2 V−1 s−1, a threshold voltage close to 0 V, and an on/off current ratio above 107. In situ lattice phonon Raman microscopy is used to study the stability of the SIP polymorph. It is found that films based on only C8O‐BTBT‐OC8 slowly evolve to the Bulk cofacial phase, significantly impacting device electrical performance. In contrast, the blended films stabilize the SIP phase, leading to devices that maintain a high performance over 1.5 years. This work demonstrates that blending small‐molecule organic semiconductors with insulating binding polymers can trap metastable polymorphs, which can lead to devices with both improved performance and long‐term stability. Organic field‐effect transistors based on thin films of a benzothieno[3,2‐b][1]benzothiophene derivative and blends of it with polystyrene are fabricated. In the films based on only the organic semiconductor a phase transformation from the metastable surface‐induced polymorph (SIP) to the bulk polymorph is found. In contrast, the blended films show an improved performance and, remarkably, stabilize the SIP polymorph.